1986
DOI: 10.1159/000249233
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Disease in Erythropoietic Protoporphyria

Abstract: A standardized hepatological investigation was performed in 9 unselected patients with erythropoietic protoporphyria (EPP). The aim of this study was to detect early liver involvement due to EPP and to determine the significance of several diagnostic procedures. Scintigraphy revealed slight enlargement of liver and spleen in all cases. Light microscopic examination of liver tissue in 7 patients showed protoporphyrin deposition in 4 and signs of fibrosis in 3 cases. Cirrhosis was not found. Electron microscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…An unexplained finding was the mild splenomegaly (22.4%) accompanied with a thrombopenia in 44.4% of the patients, which has also been reported in EPP patients without liver fibrosis using scintigraphy [11] . Although low-grade hemolysis due to PPIX and light-induced erythrocyte membrane damage could be an explanation, the small number of studies on red cell survival in patients with EPP without overt liver damage have not demonstrated a reduced erythrocyte survival time [38] .…”
Section: Article In Presssupporting
confidence: 55%
“…An unexplained finding was the mild splenomegaly (22.4%) accompanied with a thrombopenia in 44.4% of the patients, which has also been reported in EPP patients without liver fibrosis using scintigraphy [11] . Although low-grade hemolysis due to PPIX and light-induced erythrocyte membrane damage could be an explanation, the small number of studies on red cell survival in patients with EPP without overt liver damage have not demonstrated a reduced erythrocyte survival time [38] .…”
Section: Article In Presssupporting
confidence: 55%
“…Although there are no predictors for the development of progressive liver disease, mild LFT derangement, with values up to 3‐fold the upper limit of normal, is an abnormality that suggests liver involvement with greater elevation correlating with more severe liver injury . However, LFTs may be normal in patients with EPP‐related fibrosis and cholestasis . Because PPIX excretion decreases with progressive liver injury with a consequent rise in Erc‐PPIX, measuring Erc‐PPIX may identify patients with early liver involvement at risk of progression.…”
Section: Discussionmentioning
confidence: 99%
“…36 In contrast, liver biopsies from 7 cases of EPP without overt liver disease from The Netherlands showed protoporphyrin deposition and mild fibrosis in 3 cases; the remainder were normal. 48 In a separate study Cripps et al also reported protoporphyrin deposition in liver biopsy specimens Figure 1 The haem biosynthetic pathway showing the enzyme deficiency associated with porphyria cutanea tarda (PCT) and erythropoietic protoporphyria (EPP). The final step in this pathway involves the incorporation of iron into the middle of the ring structure of protoporphyrin IX to form haem.…”
Section: Cholelithiasismentioning
confidence: 98%